A SEM/EDS evaluation of debris removal of used rotary Ni-Ti endodontic files by four different cleaning solutions - Eleni Kosti; Youssef S. Al Jabbari; Aref Sufyan; Spiros Zinelis (Elsevier, 2024)
Purpose: The aim of this study was to compare the efficacies levels of four cleaning solutions for removing debris from rotary Nickel-Titanium (Ni-Ti) endodontic instruments. Materials and methods: Twelve instruments that fractured during ex vivo instrumentation were used. Fractured surfaces were investigated by SEM before and after 3, 6 and 9 min of ultrasonic cleaning in 17 % EDTA.3NaOH (Group A), 2.5 % NaOCl (Group B), Dentasept 3H Rapide (Group C) and ZymeX™ (Group D) solutions. EDS analyses of selected files from all four groups of untreated and ultrasonically cleaned samples were performed to assess the elemental composition of the alloy surfaces. Results: SEM analysis revealed that after 9 min of ultrasonic agitation, all four investigated solutions had cleaned fractured surfaces. However, some low-atomic-number regions exhibited random distributions on the fractured surfaces. EDS analyses indicated that only C was retained on surface after 9 min of ultrasonic cleaning. This finding was common in all tested groups. Conclusions: All four investigated solutions substantially removed debris from the surfaces of the Ni-Ti files and were considered appropriate for clinical practice.